2017
DOI: 10.1007/s11886-017-0863-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Biomarkers for Risk Assessment in Acute Coronary Syndromes

Abstract: Data supports clear association with risk and actionable value for non-high-density lipoprotein (Non-HDL) cholesterol and plasma ceramides in a setting of ACS. The prognostic value and clinical actionability of apolipoprotein B (apoB) and lipoprotein(a) [Lp(a)] in ACS have not been thoroughly tested, while the data for omega-3 fatty acids and oxidized low-density lipoprotein (Ox-LDL) are either untested or more varied. Measuring basic lipids, which should include Non-HDL cholesterol, at the time of presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…specifics, C16:0 and C24:0 ceramides, in both control PXR F=F and huPXR mice. Ceramides are complex sphingolipids that are components of the cell membrane and also play an important role in regulating cellular inflammatory signaling, stress responses, and apoptosis (Meeusen et al 2017(Meeusen et al , 2018Wang et al 2017). Circulating ceramide levels have been independently associated with an increased CVD risk in multiple human studies, and ceramides can also be detected in human atherosclerotic plaques (Bismuth et al 2008;Havulinna et al 2016;Laaksonen et al 2016;Meeusen et al 2018;Uchida et al 2017;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…specifics, C16:0 and C24:0 ceramides, in both control PXR F=F and huPXR mice. Ceramides are complex sphingolipids that are components of the cell membrane and also play an important role in regulating cellular inflammatory signaling, stress responses, and apoptosis (Meeusen et al 2017(Meeusen et al , 2018Wang et al 2017). Circulating ceramide levels have been independently associated with an increased CVD risk in multiple human studies, and ceramides can also be detected in human atherosclerotic plaques (Bismuth et al 2008;Havulinna et al 2016;Laaksonen et al 2016;Meeusen et al 2018;Uchida et al 2017;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids and EV are not only measurable indicator of some biological state or condition in cardiovascular disease, but also causative agents in CAD progression. Growing evidence suggests that the blood levels of ceramides are associated with the exacerbation of myocardial ischemic disease and its complications 7,40,49 . Studies on murine models revealed that pharmacological inhibition of the synthesis of ceramides prevents heart failure after myocardial ischemia, decreasing ventricular remodeling, fibrosis, and inflammatory infiltrate 8,43,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that distinct ceramide species are closely related to cardiovascular death in patients with coronary heart disease (CHD). Ceramide molecules Cer(d18:1/16:0), which is abbreviated to Cer16:0; Cer(d18:1/18:0), which is abbreviated to Cer18:0; Cer(d18:1/24:1), which is abbreviated to Cer24:1; and their ratios to Cer(d18:1/24:0), which is abbreviated to Cer24:0, have been investigated as new risk stratification factors in patients with CHD (Meeusen et al, 2017;Peterson et al, 2018). In patients with CHD, a high level of Cer16:0, low level of Cer24:0, and a high Cer16:0/Cer24:0 ratio in plasma are related directly to cardiovascular mortality (Tarasov et al, 2014;Laaksonen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%